2017
DOI: 10.1039/c6nr06266k
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic layer-by-layer construction of fibrous TMV biofilms

Abstract: As nature's choice in designing complex architectures, the bottom-up assembly of nanoscale building blocks offers unique solutions in achieving more complex and smaller morphologies with wide-ranging applications in medicine, energy, and materials science as compared to top-down manufacturing. In this work, we employ charged tobacco mosaic virus (TMV-wt and TMV-lys) nanoparticles in constructing multilayered fibrous networks via electrostatic layer-by-layer (LbL) deposition. In neutral aqueous media, TMV-wt as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…537 Toward free-standing films, we have recently demonstrated the development of detachable mesoporous films, using a combination of nanosphere lithography and electrodeposition to form nanopatterned, conducting virus–polymer arrays ( Figure 23 ). 538 To accomplish this, a hexagonally close-packed array of polystyrene (PS) latex microspheres was created using colloidal or nanosphere lithography, yielding a mesoporous architecture. A conducting poly(pyrrole-co-pyrrole-3-carboxylic acid) film was then electrochemically polymerized in the interstitial voids between the PS beads by cyclic voltammetry.…”
Section: Applications Of Virus-based Particlesmentioning
confidence: 99%
“…537 Toward free-standing films, we have recently demonstrated the development of detachable mesoporous films, using a combination of nanosphere lithography and electrodeposition to form nanopatterned, conducting virus–polymer arrays ( Figure 23 ). 538 To accomplish this, a hexagonally close-packed array of polystyrene (PS) latex microspheres was created using colloidal or nanosphere lithography, yielding a mesoporous architecture. A conducting poly(pyrrole-co-pyrrole-3-carboxylic acid) film was then electrochemically polymerized in the interstitial voids between the PS beads by cyclic voltammetry.…”
Section: Applications Of Virus-based Particlesmentioning
confidence: 99%
“…Among these researches, microbial biotemplates (e.g., Diatom , Spirulina platensis ( Sp . ),] Chlorella sp ., Yeast , Virus , Bacillus ,] Pichia pastoris , and Escherichia coli ) stand out because of their unique features, such as exquisite natural morphology, abundant species, low cost, renewable, and environmentally friendly. Using these favorable characteristics to produce micro/nanomaterials with elaborate structure and certain functional properties displays a major thrust in microtemplate research .…”
Section: Introductionmentioning
confidence: 99%
“…),] Chlorella sp ., Yeast , Virus , Bacillus ,] Pichia pastoris , and Escherichia coli ) stand out because of their unique features, such as exquisite natural morphology, abundant species, low cost, renewable, and environmentally friendly. Using these favorable characteristics to produce micro/nanomaterials with elaborate structure and certain functional properties displays a major thrust in microtemplate research . Due to the diversity of microbial species, a substantial range of application fields can be addressed, including yet not limited to drug delivery, wastewater treatment, catalysis, medical imaging, surface enhanced raman scattering (SERS), anisotropic conductive material, and energy storage …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial attempts to incorporate TMV particles into multilayers using electrostatic interactions revealed that, unlike spherical cowpea mosaic virus particles, the rods floated on top of the structures (Steinmetz et al, 2008). This problem was solved by sequentially alternating layer-by-layer application of two differently charged TMV variants yielding stable multilayer films that could be converted into free-standing TMV membranes that, in turn, could be used as tissue engineering supports (Tiu et al, 2017). One of the most rapidly advancing applications of TMV carrier templates is the preparation of surfaces that foster cell attachment and differentiation.…”
Section: Tmv-based Arrays On Solid Supports and In Miniaturized Devicesmentioning
confidence: 99%